Consumer Behaviour Towards the Reduction of Single-Use Plastic Among the Residents in Jelutong, Penang - Teo Kexin, Florence; Binti Hubadillah, Siti Khadijah (Emerging Advances in Integrated Technology, 2023)
Malaysia was ranked eighth out of the top 20 countries in terms of mismanaged plastic waste. High consumption of single-use plastic by consumers was the largest source of this issue. It is noticeably that consumers’ behaviours play a significant role to reduce the usage of single-use plastic. Hence, this research aims to identify the consumer behaviours of using single-use plastics in daily life among the residents in Jelutong, to determine the factors that influence the behavioural intention of single-use plastics reduction among the residents in Jelutong and, to identify the most significant factor that influence the behavioural intention of single-use plastics reduction among the residents in Jelutong. This research was carry out by using the Theory of Planned Behaviour (TPB). A Quantitative method which is using online questionnaire was employed and the total samples were 382 residents in Jelutong, Penang. All of the data were analysed using descriptive analysis and regression analysis through Statistical Packages for the Social Sciences (SPSS) software. The results show a positive relationship between the variable of attitude and subjective norm. Meanwhile, attitude is the most significant factor that influence the residents’ behavioural intention against lower plastic consumption. Thus, the findings of this study could provide usefulinformation that enable policymakers to implement effective strategies and address the plastic waste pollution to ensure future environmental sustainability.